An updated checklist of spiders (Arachnida, Araneae) of the protected areas of the Kherson region (Ukraine) - A.M. Iosypchuk (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія)
The protected areas of Kherson region include 84 sites of different categories, of which only one-tenth been studied in terms of spider diversity. It is advisable to use the results of long-term monitoring of flora and fauna to assess the level of conservation of protected areas, including species composition, abundance, and character of spider communities, Accordinly, a list of spider species of nine objects of the Nature Reserve Fund of Ukraine has beed compiled It includes two bdiosphere reserves, five national nature parks, and two preserves. The literature data were supplemented with the results of my research in 2021 on the territories of the Dzharylhatskyi and Oleshkivski Pisky Nature Parks. The spider fauna of the protected areas of the Kherson region includes 363 species of 30 families. Ten species Cyclosa sierrae Simon, 1870, Eresus moravicus Řezáč, 2008, Nomisia exornata (C.L. Koch, 1839), Oxyopes globifer Simon, 1876, Pirata piscatorius (Clerck, 1757), Singa semiatra L. Koch, 1867, Trochosa hispanica Simon, 1870, Zelotes tenuis (L. Koch, 1866), Erigonoplus jarmilae (Miller, 1943), Titanoeca spominima (Taczanowski, 1866) were recorded for the first time from the Kherson region. The latter two were added to the list after reviewing the collection of spiders from the Chornomorskiy Biosphere Reserve. For the first time in Ukraine, Neaetha absheronica Logunov & Guseinov, 2002 (1 male; June ‒ July 2021; 46.025905N, 32.934212E) was found in a psammophytic steppe of a wide part of the Dzharylgach Spit ('Dzharylhatskyi' NNP), which extends the northern border of the species' range. The genus Neaetha (Salticidae) is also new to Ukraine. The records of Eresus kollari Rossi, 1846, Civizelotes pygmaeus (Miller, 1943) and Minicia marginella (Wider, 1834) need to be confirmed. According to the author's estimates, the spider fauna of the Kherson region includes approximately 400 species. Among the upcoming research, it is planned to make an inventory of the spider fauna and analyze their communities to assess the impact of hostilities, as well as to update the information on the spider species diversity of the Chornomorskiy and Askania Nova Biosphere Reserves. A comprehensive sozological assessment of the areas proposed for protection, which already have detailed botanical descriptions, is expected. There is a high probability of extinction of a number of species from the above mentioned protected areas, since all the studied sites were affected by the hostilities.